Collaboration of Clustering Technique and Picture in Teaching Vocabulary - Hidayatur Rohmah (EDUVELOP, 2019)
This research was aimed to know the empirical evidence about the improvement of the students’ English vocabulary through Clustering technique and picture as a media at the First Grade Students of Madrasah Mu’alliminn Mu’allimat Bahrul ‘Ulum Tambakberas Jombang. The problem of the study was how to improve student’s English vocabulary through Clustering Technique and Picture as a media. This pre-experimental research is quantitative and the data taken from the pre-test and post-test and test sheet is used as the instrumentation. The result showed that the use of clustering technique and picture as a media in teaching vocabulary mastery increased. It can be seen from the students’ score of pre-test is 46.73, meanwhile the mean score of post-test is 73.67. The effectiveness of using this technique and media is implemented from students’ scores which are increased after learning vocabulary by using collaboration between clustering technique and picture as a media.